Knowledge Translation for Improving the Care of Deinstitutionalized People With Severe Mental Illness in Health Policy - Fulone, Izabela; Barreto, Jorge Otavio Maia; Barberato-Filho, Silvio; Carvalho, Marcel Henrique de; Lopes, Luciane Cruz (Frontiers in Pharmacology, 2020)
Background: Knowledge Translation (KT) is an effective strategy that uses the best available research evidence to bring stakeholders together to develop solutions and improve public health policy-making. Despite progress, the process of deinstitutionalisation in Brazil is still undergoing consolidation, and the changes and challenges that are involved in this process are complex and necessitate evidence-informed decision-making. Accordingly, this study used KT tools to support efforts that aim to improve the care that is available to deinstitutionalised people with severe mental disorders in Brazil. Methods: We used the Supporting Policy relevant Reviews and Trials (SUPPORT) Tools for evidence-informed health Policymaking (STP) and followed eight steps: 1) capacity building; 2) identification of a priority policy issue within a Brazilian public health system; 3) meetings with policy-makers, researchers and stakeholders; 4) development of an evidence brief (EB) that addresses the problem of deinstitutionalisation; 5) facilitating policy dialogue (PD); 6) the evaluation of the EB and PD; 7) post-dialogue mini-interviews; and 8) dissemination of the findings. Results: Capacity building and meetings with key informants promoted awareness about the gap between research and practice. Local findings were used to define the problem and develop the EB. Twenty-four individuals (policy-makers, stakeholders, researchers, representatives of the civil society and public defence) participated in the PD. They received the EB to subsidise their deliberations during the PD, which in turn were used to validate and improve the EB. The PD achieved the objective of promoting an exhaustive discussion about the problem and proposed options and improved communication and interaction among those who are involved in mental health care. The features of both the EB and PD were considered to be favourable and helpful. Conclusions: The KT strategy helped participants understand different perspectives and values, the interpersonal tensions that exist among those who are involved in the field of mental health, and the strategies that can bridge the gap between research and policy-making. The present findings suggest that policy dialogues can influence practice by promoting greater engagement among stakeholders who formulate or revise mental health policies.